IMPORTANCE OF HUMAN RESOURCE MANAGEMENT PRACTICES AND THE IMPACT COMPANIES FACE IN RELATION TO COMPETITIVE CHALLENGES (Singaporean Journal of Business Economics and Management, 2014)
AbstractThe rapidly transforming business landscape means that there are currently many human resource management challenges which will continue to evolve for years to come. As the business world changes, so does the role of HR professionals. Since human resource management is a business-driven function, effectiveness depends on a thorough understanding of the strategic corporate direction, as well as the ability to influence key policies and decisions. Due to fluctuating economic activity around the world as well as local and global advancements, there are many changes occurring rapidly that affect human resources within a wide range of issues. Human resource management challenges must be defined and solutions determined in order to succeed. Several challenges facing human resource management are discussed and the importance of human resource management practices is highlighted within the discussion.